(The effect of sterillization and storage time on the quality of canned tofu in sauce). - N. Ridwan, Indra; Rahayu, Ida; -, Hasroel; Abdurahman, Dede; -, Kosasih (Warta Industri Hasil Pertanian, 1992)
The study aimed at finding the effect of sterilization and storage time on the quality of canned tofu in sauce.The sterilization time used are 40,50,and 60 minutes at 112 degree C. Storage time are 0 (control)14,28,42 and 56 days.The result showed that the best product are obtained using 40 minutes sterilization.The protein content of the tofu is 7.9%,pH4.7,total bacteria 18 col/g/ml and vacuumness of the can is 963.7 mm Hg.The organolepticeÂ  test showed that the product is still highly accepted after 56 days of storage .